Molecular profiling of circulating tumor cells guides effective EGFR inhibitor treatment in advanced hepatocellular carcinoma: a case report - Chiu, Wei; Chen, San-Chi; Chao, Yee; Lee, Jan‐Mou (Frontiers in Oncology, 2025)
Circulating tumor cells (CTCs) hold promise for use in personalized medicine for hepatocellular carcinoma (HCC). Their abundance and molecular characteristics may predict disease prognosis and could be used to monitor responses to treatment in specific types of cancers. The present case report described a 52-year-old woman with metastatic HCC with an extensive treatment history. The patient’s CTCs demonstrated EGFR surface mutations, specifically, an EGFR exon 19 deletion and an L858R mutation. Based on this finding, the patient’s metastatic lung lesions were treated with an EGFR tyrosine kinase inhibitor-based regimen, which achieved a partial response that was confirmed using the Response Evaluation Criteria in Solid Tumors (version 1.1). Notably, the patient benefited from this therapy regimen for a period of 14 months. The progression of precision medicine in HCC has been hampered by difficulties in identifying cancer driver genes and the limited utilization of histological diagnosis. The findings of the present study suggest that molecular analysis of CTCs may have the potential to guide personalized HCC treatment strategies in the future.